Effect of Gamma- Irradiation on Structure, Morphology and Thermal Properties of Novel Polyamide Based Thermoset Obtained by Double Cycloaddition - Kalluraya, Balakrishna; B R, Kaushik; Somashekarappa, H M (Journal of Modern Materials, 2020)
Cycloaddition reactions gained prominence in macromolecular chemistry for generating macromolecules because of high yields of these reactions, which is a key tool that drives polyaddition reactions. Cycloaddition reaction plays major role in extension of polymerisation or in other words high conversions of monomers to macromolecules of high molecular weights. Until the late 1990s, the major studies regarding cycloadditions in novel polymer synthesis were related to polyaddition reactions. Since then in the field of polymer synthesis the affirmative strengths of these cycloaddition reactions have been exhibited in multi fold polymer design and headway material architecture. Future demand exists in unlatching the capacity of these novel synthetic routes for advanced applications in catalysis, separation, optoelectronics, and analytical media. Thus, we have developed an able and productive synthetic podium for the preparation of a new class of polyimide based on the double 1, 3-dipolar cycloaddition of thiasydnone with bis-maleimide. This paper reports the effect of gamma irradiation on the changes in physico-chemical properties of the polyamide based thermoset synthesised by double cycloaddition approach. The thermoset synthesized by this exclusive approach were irradiated with gamma doses in the range 10- 300 kGy. The substantial effect of gamma radiation and the structural modifications induced on the thermoset have been studied as a function of dose using different characterization techniques such as Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), differential scanning calorimetry- thermo gravimetric analysis (DSC-TGA), Field Emission Scanning Electron Microscope (FESEM) and UV-Vis Spectroscopy.